The Eye Pupil Adjusts to Illusorily Expanding Holes - Laeng, Bruno; Nabil, Shoaib; Kitaoka, Akiyoshi (Frontiers in Human Neuroscience, 2022)
Some static patterns evoke the perception of an illusory expanding central region or ‘hole.’ We asked observers to rate of the magnitudes of illusory motion or expansion of black holes and these predicted the degree of dilation of the pupil, measured with an eye tracker. In contrast, when the 'holes' were colored (including white), i.e., emitted light, these patterns constricted the pupils, but the subjective expansions were also weaker compared to the black holes. The change rates of pupil diameters were significantly related to the illusory motion phenomenology only with the black holes. These findings can be accounted for within a perceiving-the-present account of visual illusions, where both the illusory motion and the pupillary adjustments represents compensatory mechanisms to the perception of the next moment, based on shared experiences with the ecological regularities of light.